Clinical course and outcome in patients with severe dysphagia after lateral medullary syndrome. (27th February 2018) - Kim, Hyojun; Lee, Ho Jun; Park, Jin-Woo
Background: The objective of this study was to investigate the clinical course and final outcome in patients afflicted with severe dysphagia following a diagnosis of lateral medullary syndrome (LMS). Methods: The patients with severe dysphagia after LMS admitted to a rehabilitation unit were included and their respective clinical data were prospectively collected. The criteria of 'severe dysphagia' was defined as the condition that showed decreased pharyngeal constriction with no esophageal passage in a videofluoroscopic swallowing study (VFSS) and initially required enteral tube feeding. The data included VFSS findings, types of diet and postural modification, penetration-aspiration scale (PAS) and functional oral intake scale (FOIS). Results: A total of 11 patients were included and VFSS was performed every 2 weeks after stroke onset. Esophageal passage began to show at an average 34.7 ± 18.3 days, and the patients were able to begin consuming a partial oral diet with postural modification. It was 52.2 ± 21.8 days till they were advanced to a full oral diet. PAS and FOIS were significantly improved over time. Conclusions: Patients with severe dysphagia after LMS were able to tolerate a partial oral diet at about 5 weeks following onset, and they were advanced to a normal diet after 10 weeks. This clinical course might help in predicting the prognosis, as well as assist in making practical decisions regarding a rehabilitation program.